High quality audio coding using backward estimation of perceptual phenomena - Rodrigues, João Manuel (2021)
This paper presents a new audio compression algorithm that includes a nonuniform filter bank, gain-adaptive logarithmic quantizers, arithmetic entropy coding and an explicit psychoacoustic model to adapt the quantization according to perceptual considerations. Unlike existing perceptual coders, the new system is backward-adaptive, i.e: adaptation depends exclusively on already quantized samples, not on the original signal. We discuss the advantages of backward-adaptiveness and show that it can be successfully applied to perceptual coding.